Sex differences in the therapeutic effect of unaltered versus NFκB sensing IL-4 over-expressing mesenchymal stromal cells in a murine model of chronic inflammatory bone loss - Shen, Huaishuang; Kushioka, Junichi; Toya, Masakazu; Utsunomiya, Takeshi; Hirata, Hirohito; Huang, Ejun Elijah; Tsubosaka, Masanori; Gao, Qi; Li, Xueping; Teissier, Victoria; Zhang, Ning; Goodman, Stuart B. (Frontiers in Bioengineering and Biotechnology, 2022)
Wear particles from joint arthroplasties induce chronic inflammation associated with prolonged upregulation of nuclear factor kappa B (NF-κB) signaling in macrophages and osteoclasts, which leads to osteolysis and implant loosening. Mesenchymal stromal cell (MSC) based therapy has shown great potential for immunomodulation and mitigation of osteolysis in vivo, especially in the chronic phase of inflammation. We previously generated genetically modified MSCs that secrete the anti-inflammatory cytokine interleukin 4 (IL-4) in response to NF-κB activation (NFκB-IL-4 MSCs. However, whether the impact of sexual difference in the internal environment can alter the therapeutic effects of IL-4 over-secreting MSCs that simultaneously mitigating prolonged inflammation and enhancing bone formation remains unknown. This study investigated the therapeutic effects of unaltered MSCs versus NFκB-IL-4 MSCs in mitigating chronic inflammation and enhancing bone formation in male and female mice. The murine model was established by continuous infusion of polyethylene particles contaminated with lipopolysaccharide (cPE) into the medullary cavity of the distal femur for 6 weeks to induce chronic inflammation. Unaltered MSCs or NFκB-IL-4 MSCs were infused into the femoral intramedullary cavity in sex-matched groups beginning 3 weeks after primary surgery. Femurs were harvested at 6 weeks and bone marrow density (BMD) was measured with micro-computational tomography (μCT). Numbers of osteoclast-like cells, osteoblasts and macrophages were evaluated with histochemical and immunofluorescence staining. cPE-infusion resulted in severe bone loss at the surgery site, increased TRAP positive osteoclasts and M1 pro-inflammatory macrophages, and decreased alkaline phosphatase expression. MSC-based therapy effectively decreased local bone loss and polarized M1 macrophages into an M2 anti-inflammatory phenotype. In females, unaltered MSCs had a larger impact in enhancing the osteogenesis, but had similar anti-inflammatory effects compared to NFκB-IL-4 MSCs. These results demonstrated that local inflammatory bone loss can be effectively modulated via MSC-based treatments in a sexually dimorphic manner, which could be an efficacious therapeutic strategy for treatment of periprosthetic osteolysis in both genders.